2003
DOI: 10.1016/j.amjgastroenterol.2003.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Use of colonoscopy as a primary screening test for colorectal cancer in average risk people*1

Abstract: OBJECTIVEThe use of colonoscopy as a primary screening test for colorectal cancer (CRC) in average risk adults is a subject of controversy. Our primary objective was to build a predictive model based on a few simple variables that could be used as a guide for identifying average risk adults more suitable for examination with colonoscopy as a primary screening test. METHODSThe prevalence of advanced adenomas was assessed by primary screening colonoscopy in 2210 consecutive adults at least 40 yr old, without kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…[15][16][17] Various risk scores have also been developed for predicting advanced colorectal neoplasia (AN). [18][19][20][21][22][23][24] Although several studies 25,26 have reported that elevated blood lipids, the well documented CVD risk factor, and history of CVD were associated with increased risk of CRC, the majority of risk scores developed for AN did not include them into the models. 27 Recent studies have reported the associations between CVD risk assessment and risk of`1 CRN.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Various risk scores have also been developed for predicting advanced colorectal neoplasia (AN). [18][19][20][21][22][23][24] Although several studies 25,26 have reported that elevated blood lipids, the well documented CVD risk factor, and history of CVD were associated with increased risk of CRC, the majority of risk scores developed for AN did not include them into the models. 27 Recent studies have reported the associations between CVD risk assessment and risk of`1 CRN.…”
Section: Introductionmentioning
confidence: 99%
“…Although small adenomas (<10 mm) are evenly distributed [18,19], advanced adenomas are more predominant in the distal colorectum [20][21][22][23][24]. A recent analysis of more than 1.2 million CRC cases suggested that adenoma initiation rates were higher for proximal tumors, whereas growth rates were higher for distal tumors [25].…”
Section: Introductionmentioning
confidence: 99%